Blood pressure measurement in the obese patient: a comparison between non-invasive proximal forearm and radial arterial blood pressure measurement - Verkhovsky, Anna (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017.